A One‐Step Germole to Silole Transformation and a Stable Isomer of a Disilabenzene. Issue 4 (20th October 2017) - Reinhold, Crispin R. W.; Dong, Zhaowen; Winkler, Jan M.; Steinert, Henning; Schmidtmann, Marc; Müller, Thomas
Abstract: An unusual germole‐to‐silole transformation is described. As key intermediates hetero‐fulvenes are formed which rearrange to more stable bicyclic carbene analogues. The so‐formed germylenes undergo a reductive elimination yielding elemental germanium and siloles. In contrast, the analogous silylenes are stable at ambient conditions and were identified by MS spectrometry and NMR spectroscopy supported by the results of quantum mechanical calculations. These bicyclic silylenes are stable derivatives of the global minimum of the C4 Si2 H6 potential energy surface. Abstract : Always expect the unexpected : An unprecedented germole to silole transformation opened the way for the synthesis of novel bicyclic silylenes that are stable derivatives of the global minimum on the C4 Si2 H6 potential energy surface.